The Effect of COVID‑19 on the Incidence of Human Vector-Borne Infections Transmitted by Ixodid Ticks (Illustrated by the Example of Krasnoyarsk Territory) - A. Ya. Nikitin; O. V. Sorokina; E. I. Andaev; N. Yu. Kharlamp’eva; S. V. Balakhonov (Проблемы особо опасных инфекций, 2023)
In 2022, there was an increase in the incidence of tick-borne encephalitis (TBE) and ixodid tick-borne borreliosis (ITBB) in the subjects of the Russian Federation, federal districts and the country as a whole. At the same time, among people affected by ixodid ticks, the proportion of clinical forms of the diseases has increased. The aim of this study is to analyze the possible causes of the simultaneous increase in the incidence of vector-borne infections and the proportion of clinical forms among the people bitten by the ticks, using the materials on Krasnoyarsk Territory as an example. Materials and methods. We analyzed the incidence of TBE and ITBB among the people who have or haven’t had COVID‑19, the number of people affected by tick bites in 2021–2022 in Krasnoyarsk Territory. Statistical analysis is performed by standard methods of variational statistics using Excel. Results and discussion. It is shown that in the Krasnoyarsk Territory, with a decrease in the number of individuals affected by tick bites in 2022 as compared to 2021 (12216 and 13214, respectively), there was an increase in the number of cases of TBE (from 124 to 250) and ITBB (from 115 to 224), as well as the proportion of people who had clinical forms of the infections after tick bites. Among three possible explanations of the observed pattern, a decrease in the immune status of Krasnoyarsk residents who had had COVID‑19 before the contact with ticks is considered as the most likely one. Using statistical methods it was substantiated that among people with TBE and ITBB, the proportion of individuals who have had COVID‑19 is significantly higher than expected, based on the actual incidence of the Krasnoyarsk Territory population with a new coronavirus infection. Thus, COVID‑19 affects the incidence of vector-borne infections indirectly, through a change in the number of people contacts with natural stations, and directly, by changing the immune status.